The Utility of PathElective.com as a Curricular Adjunct in Laboratory Medicine Education. (28th October 2021) - Lilley, C M; Marin, M J; Wiencek, J; Fu, L; Wolniak, K; Kanakis, C E; Hermelin, D; Scordino, T; Thomas, C; Mirza, K M; Demas, C
Abstract: Introduction/Objective: PathElective.com was founded as a means of combating stagnating resident and medical student education due to halting of in-person educational activities during the COVID-19 pandemic. The site has since grown to be included in medical student and resident training programs at numerous institutions across the world, serving as a unique means of delivering high-quality and trackable laboratory medicine education. Methods/Case Report: The PathElective website was developed using Squarespace, video lectures were recorded by each professor or sourced from openly available web resources incorporating virtual slides, reading assignments, or relevant podcasts at the course director's discretion. Monthly website traffic data were obtained through Squarespace analytics for the first 11 months of the website being available (May 1, 2020, to April 22, 2021). Geographic and source data were obtained through deidentified IP address analysis built-in to Squarespace analytics. Students who registered to take the online courses were assessed before and after interacting with the course materials using a dual form crossover quiz design to prevent memorization of questions and assess comprehension. Quiz data were all anonymous and improvement was determined using a paired t-test. Comparisons between courses were made via percentage improvements. Results (if a Case Study enter NA): Over the tracking period, PathElective.com received 352, 012 page views, 73, 550 visits, 33, 225 unique visitors, and accrued 5, 815 registered users. Most of the visitors (72.8%) arrived at the site via a direct URL input, 14.9% through a search engine, and 10.6% through social media. Most visitors were from the US (43.8%) or India (11.9%). With a total of 1598 test pairs being analyzed from all clinical pathology modules, the average increase in score was 14.4% (95%, CI=10.3-18.6, p=0.0052). All courses experienced a statistically significant increase in scores except for Clinical Chemistry lesson 3.2 (7%, -1.8-15.9% CI, p=0.12). Courses were well received with a median satisfaction score was very satisfied in all six assessment categories. Conclusion: PathElective.com is a free and effective means of enhancing clinical pathology training in medical education. Students liked the online format, the quality of the lectures, and course faculty, and felt they could get help if needed. An area of improvement for this platform would be the interaction with students on social media.